Green technology policies versus carbon pricing: an intergenerational perspective - Rausch, Sebastian; Yonezawa, Hidemichi (Discussion papers, 2021)
Technology policy is the most widespread form of climate policy and is often preferred over seemingly efficient carbon pricing. We propose a new explanation for this observation: gains that predominantly accrue to households with large capital assets and that influence majority decisions in favor of technology policy. We study climate policy choices in an overlapping generations model with heterogeneous energy technologies and distortionary income taxation. Compared to carbon pricing, green technology policy leads to a pronounced capital subsidy effect that benefits most of the current generations but burdens future generations. Based on majority voting which disregards future generations, green technology policies are favored over a carbon tax. Smart "polluter-pays" financing of green technology policies enables obtaining the support of current generations while realizing efficiency gains for future generations.